OS03.5.A Characterization of the inflammatory tumor microenvironment composition in solid cancer patients with brain metastases after progression to immune checkpoint inhibitor therapy. (5th September 2022) - Starzer, A M; Kleinberger, M; Feldmann, K; Tomasich, E; Hatziioannou, T; Paiato, C; Heller, G; Kreminger, J; Traint, S; Steindl, A; Ressler, J M; Widhalm, G; et al.
Abstract: Background: Immunotherapy (IO) has changed the treatment landscape of metastatic cancer patients, however, treatment resistance is frequent. We aimed to characterize the inflammatory tumor microenvironment in brain metastases (BM) after IO to gain a deeper understanding of immunologic escape mechanisms. Material and Methods: Solid cancer patients who had BM resection after IO progression (IO cohort) were retrospectively identified. We analyzed tumor-infiltrating immune cell subsets (CD3, CD8, CD45RO, FOXP3) and expression of immune checkpoint molecules (PD-L1, PD-1, LAG-3) by immunohistochemistry. A control cohort of BM tissue samples without prior IO served for comparison (no immunotherapy cohort, NIO). Results: Twenty-eight IO patients (12/28, 42.9% females; 16/28, 57.1% males; median 61 years; 14/28, 50% lung cancer; 5/28, 17.9% melanoma; 4/28, 14.3% renal cell carcinoma; 1/28, 3.6% breast cancer; 4/28, 14.3% other cancer entities) and 57 NIO patients (28/57, 49.1% females; 29/57, 50.9% males; median 58 years; 35/57, 61.4% lung cancer; 9/57, 15.8% breast cancer; 4/57, 7.0% melanoma; 3/57, 5.3% renal cell carcinoma; 6/57, 10.5% other cancer entities) were included. IO patients had a median of one (range 0-4) systemic therapy line prior to IO. Median time from last IO application until BM resection was 5.6 months (range 0.2-49.8 months). Patients received a median number of 7 (range 1-56) IO applications (14/28, 50% PD-1-targeting IO; 8/28, 28.6% PD-L1; 2/28, 7.1% CTLA4; 4/28, 14.3% CTLA4+PD-1; 3/28, 10.7% IO+chemotherapy). No statistically significant differences in the densities of investigated TILs or PD-L1 expression between the IO and the NIO cohort were observed. Patients of the IO cohort showed higher PD-L1 expression compared to the NIO cohort (57.1 vs. 42.1%, Chi-square, p>0.05). Overall survival (OS) was similar in both cohorts, with a median OS of 11.0 months (range 5.0-17.0) in the IO cohort and 11.0 months (range 5.5-16.5) in the NIO cohort. Conclusion: Our findings show an upregulation of PD-L1 in BM occurring after prior IO therapy in the absence of other overt changes in the inflammatory microenvironment. Ongoing analyses in this cohort are investigating possible molecular driver of resistance by analyzing DNA methylation profiles of pre-and post-IO tissue samples of the IO cohort to potentially gain insights on inflammatory IO resistance mechanisms in BM patients.